2011
DOI: 10.1158/0008-5472.can-11-0368
|View full text |Cite
|
Sign up to set email alerts
|

The Tumor Suppressive MicroRNAmiR-218Targets the mTOR ComponentRictorand Inhibits AKT Phosphorylation in Oral Cancer

Abstract: The incidence of oral squamous cell carcinoma (OSCC) is rising rapidly in developed countries, posing a growing challenge due to the poor management of this type of malignancy at present. In this study, we profiled tumor suppressive microRNAs (miRNAs) that are silenced by DNA hypermethylation in OSCC using a functionbased screening approach. This approach employed a cell proliferation assay for 327 synthetic miRNAs in two OSCC cell lines. Among the 110 miRNAs identified in this set that exhibited inhibitory pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
171
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(186 citation statements)
references
References 36 publications
15
171
0
Order By: Relevance
“…[22][23][24][25] In our study, a novel function and mechanism of miR-218 was found in its targeting of Mitf 3'-UTR and suppression of melanogenesis in a normal melanocyte model of murine melan-a cells. 26 A luciferase activity assay demonstrated the direct binding of miR-218 to the 3'-UTR of the Mitf gene (Fig.…”
Section: Discussionmentioning
confidence: 57%
“…[22][23][24][25] In our study, a novel function and mechanism of miR-218 was found in its targeting of Mitf 3'-UTR and suppression of melanogenesis in a normal melanocyte model of murine melan-a cells. 26 A luciferase activity assay demonstrated the direct binding of miR-218 to the 3'-UTR of the Mitf gene (Fig.…”
Section: Discussionmentioning
confidence: 57%
“…The only miRNA that showed high expression in proliferative subtype and low expression in immunoreactive subtype is miR-218. However, recent studies suggested its role as a tumor suppressor and inhibiting cell proliferation (12,13). This suggested the complexities of miRNA regulations in different cancer types.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have demonstrated that miR-218 is downregulated in various types of cancer, including cervical cancer, gastric cancer, lung cancer, colon cancer, prostate cancer, and bladder cancer (Davidson et al, 2010;Song et al, 2010;Tie et al, 2010;Leite et al, 2011;Uesugi et al, 2011;Li et al, 2012a;Li et al, 2012b;Chiyomaru et al, 2012;He et al, 2012). However, the level of miR0218 expression, and its clinical significance in pancreatic cancer, remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…miR-218 functions as a tumor suppressor gene in various types of cancer, targeting multiple genes and regulating biological processes (Song et al, 2010;Tie et al, 2010;Uesugi et al, 2011;He et al, 2012;Li et al, 2012b;Yamamoto et al, 2013). Overexpression of miR-218 is known to inhibit cancer cell proliferation, invasion, and metastasis, and promote cancer cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation